h - Golland, Polina; Hata, Nobuhiko; Barillot, Christian; Hornegger, Joachim; Howe, Robert; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The three-volume set LNCS 8673, 8674, and 8675 constitutes the refereed proceedings of the 17th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2014, held in Boston, MA, USA, in September 2014. Based on rigorous peer reviews, the program committee carefully selected 253 revised papers from 862 submissions for presentation in three volumes. The 100 papers included in the first volume have been organized in the following topical sections: microstructure imaging; image reconstruction and enhancement; registration; segmentation; intervention planning and guidance; oncology; and optical imaging.
Microstructure imaging -- Image reconstruction and enhancement -- Registration -- Segmentation -- Intervention planning and guidance -- Oncology -- Optical imaging.
Keywords: Computer science; Health informatics; Radiology; Artificial intelligence; Computer graphics; Image processing; Pattern recognition; Computer Science; Image Processing and Computer Vision; Pattern Recognition; Computer Graphics; Artificial Intelligence (incl. Robotics).; Imaging / Radiology; Health Informatics; Electronic books